Analisis Kelayakan Ekonomi Pengelolaan Sampah Plastik Rumah Tangga Menggunakan Trichoderma sp. - Zulaika, Aidha; Soesilo, Tri Edhi Budhi; Noriko, Nita; Sahamony, Nur Fitriyani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Processing and managing plastic waste must be carried out through the application of environmental sustainability that can integrate ecology-based management and consider the social and economic dynamics known as the Socio-Ecological System (SES). This study aimed to determine the economic feasibility of household plastic waste management using Trichoderma sp. The research method used was the observation of plastic waste management in the community and secondary data processing results from field research on plastic waste processing with Trichoderma sp. Data analysis was carried out by applying economic analysis using the Benefit-Cost Ratio (BCR) analysis. Based on the economic analysis, it was found 1.29 BCR values for plastic waste processing using Trichoderma sp.